2014
DOI: 10.1186/alzrt232
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation with near infrared light mitigates Alzheimer’s disease-related pathology in cerebral cortex – evidence from two transgenic mouse models

Abstract: IntroductionPrevious work has demonstrated the efficacy of irradiating tissue with red to infrared light in mitigating cerebral pathology and degeneration in animal models of stroke, traumatic brain injury, parkinsonism and Alzheimer’s disease (AD). Using mouse models, we explored the neuroprotective effect of near infrared light (NIr) treatment, delivered at an age when substantial pathology is already present in the cerebral cortex.MethodsWe studied two mouse models with AD-related pathologies: the K369I tau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
131
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(137 citation statements)
references
References 48 publications
(94 reference statements)
6
131
0
Order By: Relevance
“…These results when taken together with those other models of neurodegeneration strengthen the notion that LLLT is a viable neuro-protective treatment for a range of neruodegenerative conditions. We believe this growing body of work provides the impetus to begin trialing LLLT as a broad base therapy for AD and other neurodegenerations [12]. Promising work was published in Japan by Kazuyoshi Zenba.…”
Section: Discussionmentioning
confidence: 99%
“…These results when taken together with those other models of neurodegeneration strengthen the notion that LLLT is a viable neuro-protective treatment for a range of neruodegenerative conditions. We believe this growing body of work provides the impetus to begin trialing LLLT as a broad base therapy for AD and other neurodegenerations [12]. Promising work was published in Japan by Kazuyoshi Zenba.…”
Section: Discussionmentioning
confidence: 99%
“…NIR treatment modestly reduced the small-size plaques, which was consistent with a previous study. 19 There was signi¯cant di®erence (p < 0.05) between the two groups for plaques measuring <20 m. And for plaques measuring !20 m, p value was bigger than 0.05. The small sample size and short duration of irradiation might contribute to large p value.…”
Section: Resultsmentioning
confidence: 99%
“…Purushothuman et al studied two mouse models with NIR treatment, and found out that NIR treatment could reduce hyperphosphorylated tau, neuro¯brillary tangles, oxidative stress markers and plaques. 19 They then extended the irradiated area to cerebellum. After one month of treatment, NIR mitigated AD-related pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations